2023
DOI: 10.1002/ijop.12918
|View full text |Cite
|
Sign up to set email alerts
|

Political violence and posttraumatic stress symptoms among Palestinians: The mediating roles of sense of belongingness and loneliness

Abstract: The current study investigated the correlation between political violence and posttraumatic stress symptoms (PTSS) and whether the sense of belongingness (SOB) and loneliness mediate the correlation between the two variables among Palestinians living in a society characterised by high political violence and prolonged traumatic events. The study sample consisted of 590 Palestinian adults, consisting of 360 men and 230 women, and were recruited using non‐probabilistic convenience sampling methods from a village … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…The results showed that most of the adolescents experienced personal trauma (N = 909, 88.4%), witnessed trauma to others (N = 861, 83.7%) and observed demolition of property (N = 908, 88.3%) during the war on Gaza, and 53.5% of the sample met DSM-V diagnostic criteria of PTSD (El-Khodary et al, 2020). Furthermore, Mahamid et al (2023) have studied the association between political conflict and posttraumatic stress symptoms among Palestinian adults and found that there was a positive correlation between political violence and signs of trauma.…”
Section: Introductionmentioning
confidence: 97%
“…The results showed that most of the adolescents experienced personal trauma (N = 909, 88.4%), witnessed trauma to others (N = 861, 83.7%) and observed demolition of property (N = 908, 88.3%) during the war on Gaza, and 53.5% of the sample met DSM-V diagnostic criteria of PTSD (El-Khodary et al, 2020). Furthermore, Mahamid et al (2023) have studied the association between political conflict and posttraumatic stress symptoms among Palestinian adults and found that there was a positive correlation between political violence and signs of trauma.…”
Section: Introductionmentioning
confidence: 97%